The Influence of Job Stress and Job Satisfaction onEmployee Turnover Intention with Organizational Commitment as an Intervening Variable at PT. Petronesia Benimel (HKI Group) - Susanto Sagita Putra, Dwi; Farida Ferine, Kiki (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to see the influence of job stress and job satisfaction on employee turnover intentions with organizational commitment as an intervening variable at PT. Petronesia Benimel (HKI Group), the type of research used is quantitative, the research was carried out at the PT Organization. Petronesia Benimel (HKI Group), the population in this research is 70 employees, the sample used is the entire population, namely 70 employees, the sampling technique used is a saturated sampling technique, the research data source uses primary data, data collection by distributing questionnaires, research model What is used is analytical tools, and the research measuring tool uses Smart PLS version 3.3. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Organizational Commitment with an original sample value of 0.787 and a p value of 0.000. Job Satisfaction has a positive and significant effect on Turnover Intention with an original sample value of 0.638 and a p value of 0.000. Organizational Commitment has a positive and significant effect on Turnover Intention with an original sample value of 0.264 and a p value of 0.029. Job Stress has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.019 and a p value of 0.849. Job Stress has a negative and insignificant effect on Turnover Intention with the original sample -0.175 and p value 0.182. Job Satisfaction has a positive and significant effect on Turnover Intention through Organizational Commitment with the original sample being 0.208 and p value 0.017. Job Stress has a positive and insignificant effect on Turnover Intention through Organizational Commitment with the original sample of 0.005 and a p value of 0.896.